Comparative Physico-Chemical Analysis of Yamuna River, Delhi, at Okhla Barrage In Pre-Monsoon & Post-Monsoon Season: A Comparative Study of Water Quality in Yamuna River, Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Developinga talented workforce is essential to sustainable competitive advantage. Hence,a company that creates a talented workforce and implements suitable qualityservice programs is likely to succeed in a globally competitive economy (Kunduand Vora, 2004). Organizations are participants in talent wars in which rewardsgo to those companies who can attract, develop, use, and retain talent globally(Brake, 2005).